um, since it's summer, i'm guessing this isn't homework, so i'll help:
6x(x+3)-2(x+3) = 6x(squared)+18x-2x-6 = 6x(squared)+16x-6
then try either (3x **)(2x**) or (6x**)(x**) and filling in the appropriate numbers
2007-06-28 07:56:24
·
answer #1
·
answered by shorty pants 3
·
0⤊
0⤋
Multiply and then add the terms.
Multiply:
-2(x + 3) = (-2)(x) + (-2)(3) = -2x -6
add the terms:
6x - 2(x+3) = 6x - 2x -6 = 4x - 6
the above can be simplified further:
4x-6 = 2(2x -3)
2007-06-28 14:54:14
·
answer #2
·
answered by Roger S 7
·
0⤊
0⤋
6x - 2(x + 3)
= 6x + (-2)(x) + (-2)(3) distributive law
= 6x + (-2x) + (-6) substitution
= 6x - 2x - 6 definition of subtraction
= 4x - 6 combine like terms
Answer: 4x - 6
2007-06-28 15:00:12
·
answer #3
·
answered by mathjoe 3
·
0⤊
0⤋
=6x-2(x+3)
=6x+12-2x+6
=6x-2x+12+6
=4x+18
2007-06-28 14:56:39
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Remove parentheses: 6x - 2x - 6 = 4x -6
2007-06-28 14:52:18
·
answer #5
·
answered by steve_geo1 7
·
0⤊
0⤋
6x-2x-6 -> 4x-6 i think that's it. you multiply the -2 by x & 3 that's the key.
2007-06-28 14:52:08
·
answer #6
·
answered by ☮ 4
·
0⤊
0⤋
-2(x+3) = -2x - 6
giving:
6x - 2x - 6 =
4x - 6
= 2(2x-3)
2007-06-28 14:51:25
·
answer #7
·
answered by miggitymaggz 5
·
0⤊
0⤋
i have a question. why do you have algebra homework if it is summer vacation?
2007-06-28 14:56:52
·
answer #8
·
answered by Cindy C 2
·
0⤊
0⤋